SEED-BORNE MYCOFLORA OF STORED RICE GRAINS AND ITS CHEMICAL CONTROL - A. R. Butt; S. I. Yaseen; A. Javaid (Journal of Animal and Plant Sciences, 2011)
Stored grains of five varieties of rice (Oryza sativa L.) viz. KS-282, Basmati-385, Basmati-370, Basmati Kernal and Basmati-198 were studied to investigate the occurrence of seed-borne mycoflora using blotter paper method. There was 27%, 19%, 17%, 16% and 14% mycoflora found associated with the seeds of Basmati kernel, Basmati-385, Basmati-370, Basmati-198 and KS-282, respectively. Four fungal species namely Fusarium moniliforme, Alternaria sp., Helminthosporium sp. and Curvularia sp. were isolated from different test rice varieties.  Four chemical fungicides namely antracal, topsin, mencozeb and derosal were used to investigate their effect on seed-borne mycoflora of rice. Seed treatment with different fungicides exhibited insignificant effect on the occurrence of F. moniliforme and Alternaria sp. Antracal completely stopped the growth of Helminthosporium sp. and Curvularia sp. The other three fungicides markedly suppressed the growth of Helminthosporium by 50%. Similarly, topsin and mencozeb suppressed the growth of Curvularia sp.by 50%.
Keywords: Chemical control; rice; seed-borne mycoflora